Pengembangan Program Perkuliahan Zoologi Invertebrata (P3ZI) Berbasis Keterampilan Berpikir Kritis - Adun Rusyana; Nuryani Y. Rustaman (Bioedukasi: Jurnal Pendidikan Biologi, 2011)
ABSTRACT- A study deals with critical thinking based model for Invertebrate Zoology instruction conducted in Biology Education of Teachers Training College was aimed to improve critical thinking  of the biology prospective teachers.  This study employed       research and development design. This study was intended to mainly provide the         prospective teachers with: a developed model of critical thinking based instructial       program, and its evaluation. The study resulted in a model of critical thinking-based      instructional program used for teaching Invertebrate Zoology. The proposed model has it strength in improving students’ both deductive and inductive thinking skills. In addition, this model is also effective to improve critical thinking in the teaching practice of certain subject covering structural morphology and anatomy. Yet, the developed model has it    limitation in terms of enhancing/promoting students’/trainees’of making assumptions and argu-ments. engembangan Program Perkuliahan Zoologi Invertebrata (P3ZI) Berbasis Keterampilan Berpikir Kritis